Recent mechanisms of surface ecological changes driven by climate change and human activities in Lake Biwa, Japan - Gao, Botong; Chen, Meng; Hao, Haichao; Yamashiki, Yosuke Alexandre; Ishikawa, Kanako; Jiao, Chunmeng; Cai, Ji; Ismail, Sadaf (Frontiers in Ecology and Evolution, 2023)
Lake Biwa, Japan represents a crucial example of the complex climatic and anthropogenic drivers influencing lake ecological transformations, vital to informing sustainable development goals globally.This study utilizes 2002-2022 Landsat, MODIS and in situ Lake Biwa monitoring data to analyze surface layer spatiotemporal dynamics across interrelated vegetation, water quality and meteorological indicators-encompassing Normalized Difference Vegetation Index (NDVI), nitrogen (N), phosphorus (P), chlorophyll-a (Chl), and water temperature (W-TEM). Upward NDVI raster trends were found over 20 years alongside prevalent N, P and Chl declines-although some increases did occur spatially in P and Chl-while W-TEM mostly rose lakewide. Southwest-northeast gradients 2 typified distributions. Further attribution analyses revealed W-TEM as the primary N, P and Chl driver, while agricultural expansion and urbanization mediated crucial N and P changes. Moreover, wind speed (WS), Crop, W-TEM, minimum temperature (TMMN), Chl and N constituted top NDVI raster influence factors respectively. These novel integrated models quantifying Lake Biwa ecological responses to multifaceted environmental change provide new perspectives to inform sustainable management of Lake Biwa itself and critical freshwater resources worldwide.